2007
DOI: 10.1369/jhc.7a7177.2007
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Microdissected Formalin-fixed and Paraffin-embedded Tissue Specimens

Abstract: Targeted proteomics research, based on the enrichment of disease-relevant proteins from isolated cell populations selected from high-quality tissue specimens, offers great potential for the identification of diagnostic, prognostic, and predictive biological markers for use in the clinical setting and during preclinical testing and clinical trials, as well as for the discovery and validation of new protein drug targets. Formalin-fixed and paraffin-embedded (FFPE) tissue collections, with attached clinical and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 54 publications
(79 reference statements)
5
130
2
2
Order By: Relevance
“…eral studies have shown that although the individual peptides retrieved and identified from fresh-frozen and FFPE tissues may differ, the biological information obtained from both types of material in terms of number of proteins identified, cellular location and molecular function is very similar (5)(6)(7)(8)(9)(10). A number of proteomics studies were reported, which used untargeted MS on FFPE tissues to compare diseased and healthy samples in the search for potential novel biomarkers (10).…”
mentioning
confidence: 99%
“…eral studies have shown that although the individual peptides retrieved and identified from fresh-frozen and FFPE tissues may differ, the biological information obtained from both types of material in terms of number of proteins identified, cellular location and molecular function is very similar (5)(6)(7)(8)(9)(10). A number of proteomics studies were reported, which used untargeted MS on FFPE tissues to compare diseased and healthy samples in the search for potential novel biomarkers (10).…”
mentioning
confidence: 99%
“…Finally, and by no means least, there is a growing body of recent literature with respect to use of AR methods for extraction of molecules (DNA, RNA, and proteins) from FFPE tissues that has further extended the utility of archival tissues and promises to allow the combination of proteomics and IHC in a true molecular morphology approach. So effective have these AR-based approaches become that investigators are now actively exploring the possible advantages of FFPE tissues in terms of preservation of both morphology and molecules in cell/tissue samples, in comparison to other methods of sample preparation (Frank et al 1996;Masuda et al 1999;Sato et al 2001;Shi et al 2002;Shi et al 2006;Palmer-Toy et al 2005;Becker et al 2007;Guo et al 2007;Jiang et al 2007;Addis et al 2009;Fowler CB et al 2010;Shi and Taylor 2010c).…”
mentioning
confidence: 99%
“…Another possible detergent is guanidin-HCl ( Jiang et al, 2007). Chaotropic agents can also be used for proteins retrieval from FFPE tissues (Guo et al, 2007). RIPA buffers were used with different amounts of NaH 2 PO 4 , NaHPO 4 , NaCl, Triton, fluoride, sodium cholate, sodium azide, and ethylenediamine tetraacetic acid (EDTA) on colorectal carcinoma (Ikeda et al, 1998), lymphoma (Crockett et al, 2005), and prostate cancer specimens (Hwang et al, 2007).…”
Section: Optimal Tissue Solubilization Towards Protein Extractionmentioning
confidence: 99%